The Idea of “Eastern Europe”: Cultural Synthesis at the Frontier with the Enemy Beyond Europe - Peluritis, Laurynas (Eidos. A Journal for Philosophy of Culture, 2025)
The paper examines Eastern Europe’s complex and often problematic identity, particularly its positioning between East and West through the philosophical, historical, cultural, and geopolitical debates and their implications of this region’s identity. The paper discusses the role of cultural synthesis in shaping national identity, specifically focusing on the work of Lithuanian philosopher Stasys Šalkauskis. Šalkauskis’ idea of Lithuania being a bridge between Eastern and Western civilizations through cultural synthesis is central to the analysis. Cultural synthesis is interpreted as a fundamental creative openness to influence and a way to integrate national and European identity. The paper also addresses the ongoing debate about Russia’s identity as being “beyond Europe,” both ideologically and politically, particularly in light of the Russian-Ukrainian conflict. This is done by engaging an ironic essay by Russian poet Josif Brodsky, and an interpretation of Russia’s war against Ukraine by historian Alexander Etkind. Through these the paper reflects on the current geopolitical context pointing to the persistent ideological and political divide, particularly regarding Russia’s stance toward the idea of Europe.